Pengaruh Daya Saing terhadap Produktivitas Kerja Para Penenun Tenun Ikat di Kabupaten Sikka - Kami, Maria; Br. Barus, Debi Angelina; Ladapase, Epifania M. (Lembaga Yasin AlSys, 2025)
The Ikat weavers in the sikka district experience low work productivity so that the weavers are not able to compete with the ikat weavers in other regions. other regions. This study aims to determine the influence of competitiveness on the work productivity of the Ikat weavers in Sikka Regency. in Sikka Regency. The population in this study is the Ikat Weavers in Sikka Regency. Ikat Weavers in Sikka Regency, using an incidental sampling sample of 240 people. Method in data collection in this study using competitiveness scale and work productivity scale.work productivity scale. Data analysis methods using normality test, linearity testlinearity test and simple regression test with the help of Spss for windows 16.0.the results of data analysis show that there is an influence of competitiveness on the work productivity of ikat weavers in Sikka Regency. The result is indicated by linearity analysis and simple regression analysis. Butikan with linearity analysis and regressive analysis obtained sig. level (2 tailed) 0.000 <0.05 the fan of the simple regression equation amounted to 7.3% which contributed that other variables to examine in this study wereother variables to examine in this study amounted to 92.7%.